The Role of Kyai Abdullah Sadjad's Sufism Education on the Spiritual Success of the Jama'at Thariqat Mulya Jati - Jati Mulya - Ifa Nurtaqiya (http://jagadalimussirry.com/, 2022)
This study aims to determine the role of Sufism education taught by Kyai Abdullah Sadjad on the spiritual success of the tariqat Mulya Jati-Jati Mulya congregation. The research method used in this research is a qualitative approach and a descriptive method. Descriptive qualitative research is a research method that seeks to describe the object under study objectively, and aims to systematically describe the facts and characteristics of the object as well as the frequency of the researched accurately. Data analysis was carried out through several stages, namely data reduction, data display and conclusion drawing/verification. The results of this study explain that the Sufism education taught by Kyai Abdullh Sadjad provides an important role for the spiritual success of the congregation of tariqat Mulya Jati-Jati Mulya. This is evidenced by the acknowledgment of several informants, that the changes in their morals during Kyai Abdullah Sadjad's Sufism education are increasingly being istiqomah in worship, always husnudhon, and tawakal. Thus, it can be concluded that Kyai Abdullah Sadjad's Sufism education has an important role in building the spiritual success of the tariqat Mulya Jati-Jati Mulya congregation. So that the existence of spiritual stability in each individual will not cause loss of vision of divinity, emptiness of soul and various other spiritual ailments.